The construction of balanced bounding-volume hierarchies using spatial object median splitting method for collision detection - Sulaiman, Hamzah Asyrani; Bade, Abdullah (The Society of Digital Information and Wireless Communications, 2011)
Finding two or more contact points between rigid bodies simulation is always a fundamental task in virtual environment. Furthermore, the contact point needs to be accurately reported as soon as possible within 30-60 frames per second (fps) between moving polyhedral. This article introduced an efficient splitting method that is able to divide the bounding-volume of Axis Aligned Bounding-Box (AABB) hierarchies into a balanced tree. The construction of well-balanced tree will helps to improve the speed of the intersection between rigid bodies’ objects.